Constraint-Based Object-Oriented Programming - Hofstedt, P (IEEE software, 2010)
The application and importance of constraint programming (CP) has grown remarkably in the past two decades. Developers widely use constraints for many planning, scheduling, and optimization tasks.Both the OO and constraint-based paradigms have advantages for certain application fields and programming techniques. Imperative OO languages such as Java and C++ let us model precisely and efficiently the behavior of state-changing systems.